Advances in databases and information systems : 21st European Conference, ADBIS 2017, Nicosia, Cyprus, September 24-27, 2017, Proceedings /: 21st European Conference, ADBIS 2017, Nicosia, Cyprus, September 24-27, 2017, Proceedings. (2017) - Unknown
No abstract available